Incidence of Prosthesis-Patient Mismatch in Valve-in-Valve with a Supra-Annular Valve - Alwan, Louhai; Ruge, Hendrik; Krane, Markus; Prinzing, Anatol; Noebauer, Christian; Lange, Rüdiger; Erlebach, Magdalena (The Thoracic and Cardiovascular Surgeon, 2022)
Background Transcatheter aortic valve replacement (TAVR) for a degenerated surgical bioprosthesis (valve-in-valve [ViV]) has become an established procedure. Elevated gradients and patient-prosthesis mismatch (PPM) have previously been reported in mixed TAVR cohorts. We analyzed our single-center experience using the third-generation self-expanding Medtronic Evolut R prosthesis, with an emphasis on the incidence and outcomes of PPM.Methods This is a retrospective analysis of prospectively collected data from our TAVR database. Intraprocedural and intrahospital outcomes are reported.Results Eighty-six patients underwent ViV-TAVR with the Evolut R prosthesis. Mean age was 75.5 ± 9.5 years, 64% were males. The mean log EuroScore was 21.6 ± 15.7%. The mean time between initial surgical valve implantation and ViV-TAVR was 8.8 ± 3.2 years. The mean true internal diameter of the implanted surgical valves was 20.9 ± 2.2 mm. Post-AVR, 60% had no PPM, 34% had moderate PPM, and 6% had severe PPM. After ViV-TAVR, 33% had no PPM, 29% had moderate, and 39% had severe PPM. After implantation, the mean transvalvular gradient was reduced significantly from 36.4 ± 15.2 to 15.5 ± 9.1 mm Hg (p < 0.001). No patient had more than mild aortic regurgitation after ViV-TAVR. No conversion to surgery was necessary. Estimated Kaplan–Meier survival at 1 year for all patients was 87.4%. One-year survival showed no significant difference according to post-ViV PPM groups (p = 0.356).Conclusion ViV-TAVR using a supra-annular valve resulted in low procedural and in-hospital complication rates. However, moderate or severe PPM was common, with no influence on short-term survival. PPM may not be a suitable factor to predict survival after ViV-TAVR.
Keywords: heart valve; transapical; percutaneous; TAVI; aortic valve and root; reoperation